Rice Gene Pool for Tarai and Inner Tarai Areas of Nepal (Nepal Agriculture Research Journal, 2010)
Knowledge on crop gene pool helps to develop varieties, to know the potential sources forbreeding materials and to develop strategy for sustainable use and conservation. The amount ofgenetic diversity presents depends on the number and diversity of the original ancestorsinvolved in the creation of a germplasm pool, existing landraces and wild species. The objectiveof this research was to study the diversity of rice gene pool present in the Nepalese improvedrice cultivars and landraces adapted to Tarai and Inner Tarai (500landraces, and 6 wild species and relatives of rice adapted to Tarai and Inner Tarai. Eightcountries are the origins for 28 cultivars. In Nepal 4 cultivars were bred and developed using alocal landrace and exotic genotypes. A total of 35 ancestors originated in 11 different countrieswere used to develop these 28 cultivars. Highest number of ancestors was from India. Use ofancestors of both sativa and nivara species having indica and japonica types indicated thecollection of wide gene pool. Most of the ancestors were sativa (60.00%) and indica (65.71%).Genetic erosion is observed in rice diversity therefore, in situ, on farm and ex situ conservationsare necessary for maintaining the genetic variation. Utilization of local landraces in breedingprogram may be the good way of genetic resources conservation. Gene pool from theselandraces along with international gene pool could make towards success in developing highyielding cultivars with wide adaptability and/or site specific. In this study, cultivars andlandraces surveyed represent a wide range of variation for different areas of origin andadaptation. This genetic diversity is very useful for further rice improvement and should beconserved both ex situ and in situ.Key words: Ancestor; Landrace; Nepalese rice cultivar; Rice gene pool; Tarai and Inner TaraiDOI: 10.3126/narj.v6i0.3339Nepal Agriculture Research Journal Vol.6 2005 pp.10-22